Islamic work ethics, komitmen afektif, dan perilaku suara karyawan: Sebuah studi pendahuluan - Ali Akhmadi; Hendryadi Hendryadi (LPMP Imperium, 2022)
This study attempts to uncover the influence of Islamic work ethic (IWE) on employee voice, which has never been explored before. The model was developed by placing IWE as an antecedent of voice behavior, and affective commitment was tested as a mediator. Data were collected using a purposive sample of 100 respondents, and PLS-SEM analyzed the data. The analysis results show that IWE positively and significantly impacts affective commitment and employee voice behavior. Affective commitment is positively related to voice behavior and may mediate the relationship between IWE and voice behavior. The results of this study are preliminary, so further research is needed to retest the resulting model.